Perancangan Sign System dengan Pendekatan Ergonomi (Studi Kasus Kampus Universitas Widyatama) - Suyono, Annisa Maharani; Rahmana, Arief; Iriani, Yani; Margana, Riki Ridwan (Universitas Mercu Buana, 2023)
The lack of proper signage and wayfinding, along with the differences in building designs within the campus of Widyatama University, often makes it difficult for visitors to find their intended locations. Therefore, the design of the signage and wayfinding system must take into consideration the following aspects. Firstly, the design should be attractive and informative, especially given the diversity of building shapes within the campus. The signage to be designed should use Widyatama University's distinctive colors and easily legible typography. In collecting data for this design, we utilized various methods such as field studies, questionnaires, interviews, observations, and documentation. With an appealing and informative signage system, it will not only facilitate navigation for visitors but also enhance the overall aesthetics of the buildings on the Widyatama campus. This is a crucial step in providing clear information and assisting everyone in finding the locations they are looking for within the Widyatama University environment.